Kajian pembentukan tegasan dan anjakan pada matalat pemotong disebabkan oleh parameter pemotong menggunakan kaedah unsur tak terhingga (FEA) - Mohd. Saad, Rozaimi (2003)
The technology growth produced many types engineering components which including various achievement of the new materials. The discovery of the new materials has been caused forming processlfinishing process of the components become complicated to make by using cutting tools. The growth of technology has been realized several of new technologies such as software that can be analyzed outputs of components before it will be commercialized. The superficial of CADICAMICAE has been changed the concept of the product manufacture which the analysis can be instants made before the high volume product will be manufacture. From the facilities such as Finite Unsurt Analysis (FEA), the components can be instant analyzed for encouraging the demands of the market in terms of quality and durability. In the research study carried out through this project, fillinf unigraphic 11 will be used to analyse the strength and adjustment required to be done on cutting tool used in the machining of the chosen metal work-piece, thats the metal having the hardness value of 45HRC maximum. Cutting tool being studied is the Carbide (K068) and Un-coated Ceramic (K090) manufactured by famous cutting tool manufacturer, KENNAMETAL.